The Banking Income Dilemma - Speagle, Richard E.; Silverman, Leo (The Review of Economics and Statistics, 1953)
THE treatment of institutions remains one of the most unsatisfactory areas in national income accounting. Standing at the end of a long process of evolution in both concepts and methods, the recognized experts in the field are still compelled to admit that their procedures, best exemplified today by those of the United States Department of Commerce, remain open to much basic criticism.' This paper proposes to reformulate the current treatment of bank income, including a reopening of the discussion of financial intermediaries in their role as contributors to the national income and product. It is believed that the methodology suggested here is simpler, more in accord with reality, theoretically sounder, and of greater analytical value in deriving series of bank income and, ultimately, of productivity estimates. In the beginning of this study, the concepts proposed and those now in use by the Department of Commerce will be described.2 As a second step, the two opposing methods will be examined for their underlying rationale and philosophy. Third, technical procedures will be compared by means of simplified accounting models. Fourth, a number of refinements and qualifications both of principle and technique will be introduced, which are important in facilitating the passage from didactic framework to the final statistical series of income and product originating in banking. These series, if they are to be useful, must be capable of being integrated into the total national accounts. How this can be done will be demonstrated at various points along the way. I